Electroacoustic Quantification of Surface Bound Ligands in Functionalized Silica and Iron Oxide Nanoparticles. Issue 40 (25th October 2019) - Renner, Alexander M.; Schütz, Markus B.; Moog, Daniel; Fischer, Thomas; Mathur, Sanjay
Abstract: The electrokinetic sonic amplitude (ESA) is one of the most versatile techniques for deriving the zeta potential of nanoparticles before, during and after surface functionalization with different ligands, thus overcoming current limitations of well‐established electrophoretic measurement principles. We present a novel method for direct quantification of accessible hydroxide groups available on the surface of silica nanoparticles by the ESA effect, supported by simultaneous electrical conductivity measurements. Moreover, the in‐operando determination of varying zeta potential during addition of carboxylic acids demonstrate a profound way to quantify surface‐bound ligands, which still poses a challenge in following the surface modification of nanoparticles. In this study, phase pure cuboidal hematite particles were chosen as a model system with an initial zeta potential between +50 and +55 mV in ethanol. Using both citric acid and 10‐undecynoic acid as surface‐modifiers, the correlation between the degree of surface functionalization and zeta potential was investigated. The decrease of zeta potential of hematite particles during the titration of 10‐undecynoic acid or citric acid could be directly correlated to a successful surface functionalization in contrast to a surface protonation, which would be expected in case of both carboxylic acids. Furthermore, the addition of 10‐undecynoic acid led to a stabilization effect on the zeta potential of cuboidal hematite particles. These results highlight the hitherto unexplored potential of ESA techniques as a quantification method in nanoparticle surface modification. Abstract : Quantification of functional groups and bound surface ligands of silica and iron oxide nanoparticles is investigated utilizing the electrokinetic sonic amplitude effect supported by simultaneous electrical conductivity measurements. Therefore, cuboidal hematite particles were chosen as a model system with an initial zeta potential between +50 and +55 mV in ethanol.